Pharmacokinetic and Pharmacologic Characterization of the Dihydrotetrabenazine Isomers of Deutetrabenazine and Valbenazine. Issue 4 (18th December 2022) - Brar, Satjit; Vijan, Arjun; Scott, Fiona L.; Jimenez, Roland; Zhang, Hui; Grigoriadis, Dimitri E.; Loewen, Gordon
Abstract: Valbenazine and deutetrabenazine are vesicular monoamine transporter 2 (VMAT2) inhibitors approved for tardive dyskinesia. The clinical activity of valbenazine is primarily attributed to its only dihydrotetrabenazine (HTBZ) metabolite, [+]‐α‐HTBZ. Deutetrabenazine is a deuterated form of tetrabenazine and is metabolized to four deuterated HTBZ metabolites: [+]‐α‐deuHTBZ, [+]‐β‐deuHTBZ, [−]‐α‐deuHTBZ, and [−]‐β‐deuHTBZ. An open‐label, crossover study characterized the pharmacokinetic profiles of the individual deuHBTZ metabolites, which have not been previously reported. VMAT2 inhibition and off‐target interactions of the deuHTBZ metabolites were evaluated using radioligand binding. The only valbenazine HTBZ metabolite, [+]‐α‐HTBZ, was a potent VMAT2 inhibitor, with negligible affinity for off‐target dopamine, serotonin, and adrenergic receptors. Following deutetrabenazine administration, [−]‐α‐deuHTBZ represented 66% of circulating deuHTBZ metabolites and was a relatively weak VMAT2 inhibitor with appreciable affinity for dopamine (D2S, D3 ) and serotonin (5‐HT1A, 5‐HT2B, 5‐HT7 ) receptors. [+]‐β‐deuHTBZ was the most abundant deuHTBZ metabolite that potently inhibited VMAT2, but it represented only 29% of total circulating deuHTBZ metabolites. The mean half‐life of [+]‐α‐HTBZ (22.2 hours) was ∼3× longer than that of [+]‐β‐deuHTBZ (7.7 hours). These findings are similar to studies with tetrabenazine, in that deutetrabenazine is metabolized to four deuHTBZ stereoisomers, the most abundant of which has negligible interaction with VMAT2 in vitro and appreciable affinity for several off‐target receptors. In contrast, valbenazine's single HTBZ metabolite is a potent VMAT2 inhibitor in vitro with no discernible off‐target activity. Determination of the effects of intrinsic/extrinsic variables on deutetrabenazine's safety/efficacy profile should incorporate assessment of the effects on all deuHTBZ metabolites.